Chyle leak after laparoscopic cholecystectomy in a patient with necrotizing pancreatitis: reporting a rare case - Choudhury, Nowraj Alam; Jyoti, Vidur; Yadav, Rahul (International Surgery Journal, 2025)
Chyle leak after laparoscopic cholecystectomy is an extremely rare post operative complication, usually related to inadvertent lymphatic injury in patients with distorted anatomy. We report a 70-year-old male with type 2 diabetes mellitus, hypothyroidism, and a recent history of necrotizing pancreatitis, who underwent elective laparoscopic cholecystectomy. Intraoperatively, frozen Calot’s anatomy and dense adhesions were encountered. A postoperative subhepatic drain revealed milky fluid, which was confirmed biochemically as chyle. The patient was successfully managed conservatively with dietary modifications, medium-chain triglyceride supplementation, and octreotide. Although rare, chyle leak should be considered in patients with postoperative milky drain output after laparoscopic cholecystectomy. Conservative management is effective in most cases, but requires early recognition, multidisciplinary input, and close follow-up.